The dynamics of occupational choice : theory and evidence - Drost, Andre [Verfasser] (My University, 2002)
"In this paper we provide new empirical and theoretical insights into the dynamics of occupational choice. In the empirical part of the paper we analyse West German time series data on the number of first-year students in more than 50 fields. We show that this number is cyclical in many fields so that occupational choice is cyclical in many professions. In the theoretical part we develop a model that explains cycles in occupational choice. Unlike other models, it is not based on the unrealistic assumption that occupational choice is independent of the risk of unemployment associated with each occupation." (author's abstract, IAB-Doku) ((en))
Keywords: S 1.4 Hochschulbildung; T 4.6 Wirtschafts- und Rechtswissenschaften; Berufswahl; Einflussfaktor; Studienfachwahl; Entwicklung; Bildungsökonomie; Arbeitslosigkeit; Quantitative Angaben; 1976-1991